DIGITAL MARKETING SEBAGAI STRATEGI KOMUNIKASI PEMASARAN “WAROENK ORA UMUM” DALAM MENINGKATKAN JUMLAH KONSUMEN - Ascharisa Mettasatya Afrilia (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2018)
Purwokerto is the capital of Banyumas Regency as a growing and developing small tow. Purwokerto has experienced population transformation in terms of both quantity and quality. Based on statistical data can be seen that the population in the city per year 2014 ranged between 292,782 people with an area of 38.58 KM². The increase of population per year is also increasing along with the number of migrant population. This is an opportunity for business people are no exception to the culinary business. Waroenk Ora Umum is one type of culinary business which is quite rapid growth in the city of Purwokerto. Along with the current milenal era, it is necessary to further explore the marketing strategy of targeted marketing communications. And digital marketing is one strategy that has enough impact to increase the number of consumer culinary business in this era. This study used qualitative research methods. Data collection is done by observation, documentation, and interview. The results show that Waroenk Ora Umum Purwokerto has utilized digital marketing strategy which is also balanced with other marketing strategies.